Evaluasi Penggunaan Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SIAPIK) dalam Pencatatan Laporan Keuangan Bagi UMKM di Kota Balikpapan - Nadhifa Alinza Lukyana; Miswaty; Yanzil Azizil Yudaruddin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to identify the obstacles faced by MSME actors and their perceptions of the SIAPIK application. The method used is descriptive with a qualitative approach in the form of a case study, which aims to provide a comprehensive and in-depth description of the conditions or phenomena at hand. This research also conducted several data collection techniques such as observation, interviews, and documentation. Data analysis is carried out in 4 (four) stages, namely, data collection, data reduction, data presentation, and conclusion drawing. Based on the result of the study, it shows that the SIAPIK application provides convenience in preparing detailed financial reports. However, there are 6 (six) obstacles faced by several MSME actors, namely the SIAPIK application does not accommodate tax calculations, the SIAPIK applications is not integrated with online sales, the SIAPIK application in the process of entering raw material data, the SIAPIK application does not support sales order-based sales recording, lack of user understanding of the SIAPIK application, and user experience with the SIAPIK application which often occurs server down. By identifying these obstacles, this research provides recommendations for solutions to help MSME actors overcome these obstacles and become input for Bank Indonesia in developing the SIAPIK application in the future.